Are recruiters driving gender segregation? : Evidence from the German apprenticeship market - Minßen, Luisa [Verfasser]; Levels, Mark [Verfasser]; Pfeifer, Harald [Verfasser]; Wehner, Caroline [Verfasser] (My University, 2025)
"Potential drivers of gender discrimination are recruiters, who are more likely to select applicants with characteristics similar to their own. This study explores whether recruiter characteristics (age, gender, and job position) drive gender discrimination in the recruitment of apprentices for gender-segregated occupations. A factorial survey experiment among 1872 firms in Germany estimates recruiters’ heterogeneous gender choices in male, female, and gender-mixed occupations. The study finds that female applicants are chosen less often for male-dominated occupations and more often for female-dominated occupations than male applicants. Moreover, older recruiters and firm owners are less likely to recruit female applicants for male-dominated occupations but more likely to recruit them for female-dominated occupations than younger recruiters and non-firm owners. By contrast, younger recruiters and HR professionals are more likely to recruit gender-neutrally to an occupation’s dominating gender than older recruiters and non-HR professionals. This study shows that apprenticeship applicants of a gender opposed to the dominant gender of an occupation have a disadvantage in the apprenticeship market and that certain recruiters’ characteristics further impact this disadvantage." (Authors' abstract, BIBB-Doku)
Keywords: S 5.3 Personalentwicklung; G 2.4.5 Gender Mainstreaming; 370; 300; Ausbildungsstellenbewerber; Personaleinstellung; Benachteiligung; Geschlechtsspezifische Faktoren; Geschlechtersegregation; Personalabteilung; Führungskraft; Persönlichkeitsmerkmal